Visualization Platform Design and Implementation of Water Conservancy Engineering Based on UE5 - QIU Yuke; CHEN Bingqing; CHEN Jiewen (Renmin Zhujiang)
Given the high programming technology threshold of mainstream 3D interactive development tools and insufficient visualization application in the water conservancy business, this paper carries out visualization platform design and application.Combined with the requirements of water conservancy projects, the technical visual platform route based on the UE5 graphics engine is proposed, and the interaction function is developed by calling the encapsulated programming language module via the blueprint editor.This platform not only has exquisite and intuitive scene effects with smooth loading, but also achieves core functions such as user interface management, roaming position switching, weather and day-night adjustment, and simulation of engineering equipment operation.The application of research results in multiple water conservancy projects improves the efficiency of 3D interactive function development and the diversity of implementation methods.Meanwhile, assistance is provided for the engineering design, construction, operation, and maintenance stages, which enables the digital twin construction of water conservancy engineering.